The Determinants of ESG Data Requirements for SMEs in the European Union: Insights and Challenges from Hungary - Sebestyén, Dorottya (Sustainable Governance in the Age of Artificial Intelligence: Interdisciplinary Perspectives on ESG, Digital Transformation and Corporate Responsibility, 2026)
Environmental, Social, and Governance (ESG) reporting obligations formally target large corporations, yet small and medium-sized enterprises (SMEs) increasingly encounter indirect but consequential ESG information requirements. This study examines how EU non-financial governance regulation has evolved from voluntary disclosure practices into a structured policy architecture that progressively embeds SMEs through spillover mechanisms. The analysis is based on a structured review of key EU legislative instruments–including the transition from the Non-Financial Reporting Directive (NFRD) to the Corporate Sustainability Reporting Directive (CSRD), the 2025 Omnibus simplification package, and the Voluntary Sustainability Reporting Standard for SMEs (VSME)–interpreted in light of relevant academic scholarship. The findings show that SME exposure is systemically driven through value chain transmission, financial governance dynamics, and policy recalibration. In Hungary, limited reporting capacity and interpretative uncertainty intensify these challenges. The study argues that while the VSME approach may enhance proportionality, effective implementation depends on policy coherence and strengthened organizational capabilities.